2018
DOI: 10.1016/j.jadohealth.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Prescription Drug Misuse, Sexual Violence, and Dating Violence Among High School Youth

Abstract: Purpose: Sexual violence (SV), teen dating violence (TDV), and substance use are significant public health concerns among U.S. adolescents. This study examined whether latent classes of baseline alcohol and prescription drug misuse longitudinally predict SV and TDV victimization and perpetration (i.e., verbal, relational, physical/threatening, and sexual) 1 year later. Methods: Students from six Midwestern high schools (n = 1,875; grades 9 11) completed surveys across two consecutive spring semesters. Latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 23 publications
1
29
0
7
Order By: Relevance
“…7 With respect to prescription drug misuse, one study linked SV victimization of adolescent girls by a peer to increased likelihood of nonmedical use of prescription drugs 8 ; another found that male and female youth who used alcohol and misused prescription drugs in middle school were more likely to be SV victims in high school compared with youth who only used alcohol. 9 A third study of a national sample of high school students found that for male students, only sexual dating violence was positively associated with nonmedical use of prescription drugs, whereas experiencing both physical and sexual dating violence was positively associated with nonmedical use of prescription drugs for both sexes. 10 Although these studies as a whole suggest an association between SV victimization and substance use, sexual and mental health indicators, and academic performance, there is limited information using nationally representative samples on associations of SV victimization and motor vehicle-related risky behaviors (e.g., texting and driving) or other concerning health experiences (e.g., being overweight or obese).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 With respect to prescription drug misuse, one study linked SV victimization of adolescent girls by a peer to increased likelihood of nonmedical use of prescription drugs 8 ; another found that male and female youth who used alcohol and misused prescription drugs in middle school were more likely to be SV victims in high school compared with youth who only used alcohol. 9 A third study of a national sample of high school students found that for male students, only sexual dating violence was positively associated with nonmedical use of prescription drugs, whereas experiencing both physical and sexual dating violence was positively associated with nonmedical use of prescription drugs for both sexes. 10 Although these studies as a whole suggest an association between SV victimization and substance use, sexual and mental health indicators, and academic performance, there is limited information using nationally representative samples on associations of SV victimization and motor vehicle-related risky behaviors (e.g., texting and driving) or other concerning health experiences (e.g., being overweight or obese).…”
Section: Introductionmentioning
confidence: 99%
“…3 Several studies have connected health risk behaviors in adolescence to an SV victimization history. [4][5][6][7][8][9] For example, one study 4 found male and female adolescent SV victims were significantly more likely than nonvictims to report risky sexual behaviors (e.g., multiple sex partners and sex resulting in pregnancy). Another study 5 found that SV was associated with teenage girls' binge drinking during the past 2 weeks, drinking at an early age, past-30-day marijuana use, and having sex without using birth control.…”
Section: Introductionmentioning
confidence: 99%
“…Emerge a necessidade de conhecer os fatores de risco e vulnerabilidades que afetam os adolescentes e oportunizar discussões no cenário escolar para o compartilhamento dos conhecimentos e experiências na perspectiva de uma formação cidadã (18,53,54).…”
Section: Métodosunclassified
“…A exposição à violência sexual pode levar ao baixo desempenho escolar e, consequentemente, ao uso de álcool e/ou drogas. O enfermeiro, em articulação com outros profissionais da saúde e da educação, deve reconhecer o contexto no qual o indivíduo está inserido e intervir positivamente nos aspectos que levam à transgressão dos direitos (54,55). A enfermagem possui papel central na execução dessas ações junto à escola, possibilitando uma comunicação estratégica interdisciplinar que envolva os setores da saúde e da educação (2).…”
Section: Métodosunclassified
“…A literatura indica que a maioria dos casos de abuso sexual contra crianças e adolescentes são cometidos por conhecidos da vítima, destacando-se os casos de violência sexual nas relações amorosas dos adolescentes (Costa, Miranda, Rodrigues, & Mascarenhas, 2018). A violência nas relações de namoro de adolescentes se tornaram preocupações significativas de saúde pública, incluindo atividade sexual não consentida com ou sem penetração, assédio sexual e tentativas de obtenção de atividade sexual, com prevalências observadas, nos Estados Unidos, de 15,6% no sexo feminino e 5,4% no sexo masculino (Espelage, Davis, Basile, Rostad, & Leemis, 2018).…”
Section: Introductionunclassified